Fluoride-triggered phase transition of metallogels for on-demand in situ containment of fluids - Kim, Junghwan; Kim, Chungryeol; Lee, Dongwhan (Royal Society of Chemistry, 2024)
Sol-gel transition regulates mass transport in fluidic systems. We designed pre-gelators that react with fluoride anions to form a metallogel barrier. A combination of spectroscopic, rheological, and X-ray spectroscopic studies elucidated the mechanism of gelation involving desilylation followed by metal coordination-driven self-assembly, the kinetics of which can be finely controlled by the chemical structure of the silyl substituents. Protonation-induced degelation restores flow, allowing the metallogel to function as a reversible chemical valve.